The emperor's code [compact disc, unabridged] - Korman, Gordon (39 clues, 2010)
Sibling duo Amy and Dan are forced to outwit thousands of highly skilled soldiers to steal the next clue. But when they are separated, the entire mission is threatened to be derailed.